Numerical analysis of the operating characteristics of a large‐scale CFB coal‐gasification reactor with the QC‐EMMS drag model. (15th December 2020) - Liu, Yang; Huo, Pengju; Li, Xiaohong; Qi, Haiying
Abstract: The operating characteristics of a 60 m high industrial circulating fluidized bed (CFB) coal‐gasification reactor were investigated numerically based on the Eulerian‐Eulerian approach. The QC‐EMMS drag model was used to describe the gas‐solid drag reduction caused by particle clusters. The simulations predicted the overall characteristics of fluidization and gasification inside the CFB reactor riser. The simulated results are in agreement with measured data from the field test. Then, the numerical model was used to analyze the influences of the steam/coal ratio, pulverized coal‐particle size, and operating pressure. The results show that each of the three operating parameters has a great impact on different performance parameters, such as the solid mass circulation rate, the H2 /CO ratio, the effective syngas yield, and the average bed temperature. The predicted data were then correlated to provide supports for optimizing the operations of large‐scale CFB coal gasifiers.